Screening of Antifungal Activity of Holarrhena antidysenterica and Maduca longifolia against fungal pathogens in Apple fruit - Baviskar RN; Dekate HM (International Journal of Life Sciences, 2016)
The present study aims to investigate the effect of some easily available medicinal plants on fungal pathogens. Holarrhena antidysenterica and Maduca longifolia ethanolic extracts was observed at different concentrations ranging between 500, 1000, 1500, 2000, 2500, 3000 μg/ml were tested for antifungal activity in vitro on Penicillium expansum, Aspergillus fumigatus and Alternaria alternata isolated from naturally infected apple fruit. Both plants were collected from different places of Maharshtra and identified. Ethanolic extracts of plants were assessed for antifungal susceptibility using dilition method. Known antifungal agents were used as positive control. The water extracts used as control and it was observed that the ethanolic extracts concentrations were more effective and showed antifungal activity against the test pathogens. The results reveled that Holarrhena antidysenterica showed 99% mycelial growth inhibition at 3000μg/ml against Penicillium expansum and Aspergillus fumigatus whereas Maduca longifolia showed 100% mycelial growth inhibition at 3000μg/ml against Alternaria alternata. Hence, the plant extracts possess antifungal properties that can be exploited as an ideal treatment for future plant disease management to eliminate fungal spread.